1975
DOI: 10.1136/adc.50.8.648
|View full text |Cite
|
Sign up to set email alerts
|

District paediatric day care.

Abstract: Although there have been several recent papers published on the results of day case surgery in children, little has been written on hospital-based day care for medical problems; in spite of this lack of information we believe many paediatric units provide this service. This paper describes our attempts to organize medical day cases on a general paediatric ward, and analyses some problems encountered. It is written in the hope that it will stimulate others to report their experience in this field. Experience in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Such innovative proposals have a long history and are in line with the National Service Framework for Children 2 9 10. A recent systematic review showed that ambulatory care is becoming an acceptable alternative to inpatient admission, but that more research on impact is required 7…”
mentioning
confidence: 99%
“…Such innovative proposals have a long history and are in line with the National Service Framework for Children 2 9 10. A recent systematic review showed that ambulatory care is becoming an acceptable alternative to inpatient admission, but that more research on impact is required 7…”
mentioning
confidence: 99%